Nanoparticles Targeting STATs in Cancer Therapy - Milad Ashrafizadeh; Zahra Ahmadi; Niranjan G. Kotla; Elham Ghasemipour Afshar; Saeed Samarghandian; Ali Mandegary; Abbas Pardakhty; Reza Mohammadinejad; Gautam Sethi (Cells, 2019)
Over the past decades, an increase in the incidence rate of cancer has been witnessed. Although many efforts have been made to manage and treat this life threatening condition, it is still one of the leading causes of death worldwide. Therefore, scientists have attempted to target molecular signaling pathways involved in cancer initiation and metastasis. It has been shown that signal transducers and activator of transcription (STAT) contributes to the progression of cancer cells. This important signaling pathway is associated with a number of biological processes including cell cycle, differentiation, proliferation and apoptosis. It appears that dysregulation of the STAT signaling pathway promotes the migration, viability and malignancy of various tumor cells. Hence, there have been many attempts to target the STAT signaling pathway. However, it seems that currently applied therapeutics may not be able to effectively modulate the STAT signaling pathway and suffer from a variety of drawbacks such as low bioavailability and lack of specific tumor targeting. In the present review, we demonstrate how nanocarriers can be successfully applied for encapsulation of STAT modulators in cancer therapy.